Analysis of the Structure of Job Offers on the Czech Labour Market - Tomáš Martínek; Petr Hanzlík (Review of Economic Perspectives, 2014)
Labour market development is an important macro-economic indicator of every national economy. Labour supply in particular fields should reflect on demands of employers on newly recruited employees. These demands can be analysed by studying published job offers. This analysis of Czech labour market is conducted based on the aggregated statistical data collected by an on-demand application. The studied data sample covers more than 60% of all the job offers published in the Czech Republic. The situation in respective occupational fields is compared with aggregate nation-wide average as well as with data from other fields. Results show distinct differences in absolute quantity of offers, compensations to employees offered as well as qualification requirements.
Keywords: 330